2001
DOI: 10.1103/physrevc.64.014307
|View full text |Cite
|
Sign up to set email alerts
|

Two-phonon γ-vibrational strength in osmium nuclei

Abstract: Collective E2 strengths were measured to probe the two-phonon ␥-vibrational character of I K ϭ4 4 ϩ states for 188,190 Os. Lifetimes for states with spin up to 8 ϩ of the ground-state band, 6 ϩ of the ␥ band, and the 4 ϩ state of the K ϭ4 ϩ band were measured by the recoil-distance method following Coulomb excitation by a 58 Ni projectile at E lab ϭ275 MeV. These lifetime data are compared with the electromagnetic matrix elements measured by previous Coulomb excitation experiments. The good agreement between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It was also found that the ratio of the intrinsic E2 matrix elements between the 4 + 3 and the 2 + γ bandhead approaches the harmonic limit [6]. The two-phonon γ -vibrational nature of the 4 + states found further confirmation in recent lifetime measurements, which produced E2 strengths consistent with the data obtained in the Coulomb excitation experiments [7].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…It was also found that the ratio of the intrinsic E2 matrix elements between the 4 + 3 and the 2 + γ bandhead approaches the harmonic limit [6]. The two-phonon γ -vibrational nature of the 4 + states found further confirmation in recent lifetime measurements, which produced E2 strengths consistent with the data obtained in the Coulomb excitation experiments [7].…”
Section: Introductionmentioning
confidence: 72%
“…In principle, the strength gets contribution from both the "allowed" transitions involving the one-phonon components |i, K π = 0 + of the QPM state (7) and the "forbidden" transitions from the ground to the twophonon components |[v 1 v 2 ] 0 + . In practice, the two-phonon contribution is negligible, so that the full strength is carried by the one-phonon allowed transitions, whose amplitudes are given by…”
Section: B Qpm Eλ Transition Strengths and Transfer Reaction Spectromentioning
confidence: 99%
“…In this context, the even-even 186−192 Os isotopes have been the subject of a long-standing controversy regarding the character of their low-lying excited states. In a large number of studies employing different experimental techniques such as Coulomb excitation [1][2][3], (p, p ) and (α,α ) scattering [4][5][6][7], and ( 3 H,α), ( 3 He,d), and (d, 3 He) reactions [8][9][10], apparently conflicting results have been obtained, indicating, respectively, a multiphonon quadrupole, proton two-quasiparticle, and hexadecapole character of the low-lying 4 + 3 states in these nuclei. From the theoretical side, very recently the triaxial rotor model [11], the Bohr-Mottelson collective model for a soft triaxial nucleus [12], and the quasiparticle-phonon model [13] have been employed to shed light on the nature of these states; in particular, the latter study came to the conclusion that the 4 + 3 states are indeed of a mixed nature and that all experimental results can be explained naturally in a consistent way.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier single-proton transfer study did not perform angular distributions and published a single spectrum from the 187 Re( 3 He, d) 188 Os reaction at 40 • [7]. The B(E2) values were confirmed through lifetime measurements [19], and they sparked considerable debate [7,20,21] over which component in the wave function is dominant. This debate has been dormant for several years, but recent theoretical developments may provide vital clues to the understanding of the 4 + 3 levels.…”
Section: Introductionmentioning
confidence: 99%